Current situation and improvement strategy of postgraduate training in Clinical Pharmacy - Zunpeng SHU; Yanni YANG; Zihe DING; Renxing ZHONG; Tianyi XIA; Yi WANG (Journal of Holistic Integrative Pharmacy)
[Abstract]: In the context of the Healthy China initiative, this study outlined the current situation of clinical pharmacy education in China and analyzed the major impediments in postgraduate professional degree programs in clinical pharmacy to the fulfillment of the needs of the rapid progress in China's medical and health sector and to the swift and effective improvement of the development of high-level clinical pharmacy talents. These problems are illustrated by indefinite training objectives, the lack of standardized training criteria, and the failure to change the mindset of pharmacy education and have resulted in an incomplete knowledge system and a disconnect between the training objective and the needs of society and the pharmacy industry. Therefore, the graduates as clinical pharmacists are not professional enough, with inadequate social recognition. This study advocates that educators should change the education philosophy, come up with innovative approaches toward talent training for postgraduate professional degrees in clinical pharmacy, accelerate the effective connection between talent training and registered qualification, and nurture the quality of humanism. This way, high-level talents of clinical pharmacy will be prepared, who can then cater to the needs of society and the pharmacy industry.